Mediators between perfectionism and eating disorder psychopathology in a community sample - Joyce, F.; Watson, H.; Egan, Sarah; Kane, Robert (Pergamon, 2012)
The aim of this study was to investigate the mediating effect of shape and weight overvaluation and conditional goal-setting on the relationship between perfectionism and eating pathology among women in the general community. Results from structural equation modeling indicated that the full mediation model previously established with a clinical sample (Watson et al., 2011), generalized to the present community sample (n = 202). The indirect effect of self-oriented perfectionism on eating disorder pathology was .25 (p < .001) via shape and weight overvaluation, and .10 (p < .01) via conditional goal-setting, supporting the hypothesis that self-oriented perfectionism increased eating disorder psychopathology via each mechanism. Shape and weight overvaluation was the stronger mediator. The findings provide evidence to support existing cognitive-behavioral formulations of eating pathology and clinical perfectionism, and have implications for the prevention of eating pathology.